Mathematical analysis of Hepatitis B virus infection with logistic growth for proliferation of Hepatocytes cells - Idris, Laminu; Abdulrahman, Sirajo (International Journal of Mathematical Analysis and Modelling, 2026)
A logistic growth model was developed which investigates the proliferation of hepatocytes cells for hepatitis B virus infection. The results from the model analysis show that the disease-free equilibrium (DFE) is globally asymptotically stable (GAS) when the basic reproduction number (R0) is equal to or below a unity value, and unstable when it is above the unity value. It also reveals that when R0 is above the unity value with some conditions an endemic equilibrium of the model is GAS, indicating a real proliferation of the hepatocytes cells within the boundary of the liver. Numerical simulations are also carried out using maple software to illustrate the effects of fulminant, acute and chronic infections on the number of HBV, healthy and infected (unhealthy) hepatocytes.